2022
DOI: 10.1371/journal.pone.0270570
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the scales: Preliminary investigation of total energy expenditure and daily metabolizable energy intake in Matschie’s tree kangaroo (Dendrolagus matschiei)

Abstract: Matschie’s tree kangaroo (Dendrolagus matschiei) is an endangered arboreal marsupial native to Papua New Guinea. Detailed field studies of its behavior and ecology are scarce due largely to its occupation of remote cloud forests and cryptic nature. Although this species has been in human care since the 1950s, much of its biology is still unknown. The current ex situ population is not sustainable due to health and reproductive problems, believed to stem largely from issues with diet and obesity. To better asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…One example of such practice is the provisioning of leafy or woody browse. In most facilities, browse is given as part of an enrichment regime, though some institutions now use browse as a staple diet item for various herbivorous species (Campbell et al, 2001;Dunham et al, 2022;Hatt & Clauss, 2006;Hatt et al, 2005;Nijboer & Dierenfeld, 1996;Nijboer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…One example of such practice is the provisioning of leafy or woody browse. In most facilities, browse is given as part of an enrichment regime, though some institutions now use browse as a staple diet item for various herbivorous species (Campbell et al, 2001;Dunham et al, 2022;Hatt & Clauss, 2006;Hatt et al, 2005;Nijboer & Dierenfeld, 1996;Nijboer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the ecology of herbivores is crucial for developing strategies that promote their sustainability [ 1 ]. As a fundamental aspect of ecological research, diet contributes to the substantial body size variation observed in herbivore populations [ 2 ] and provides valuable basic information for estimating environmental capacity [ 3 ], calculating energy metabolism [ 4 ], assessing habitat suitability [ 5 ], analyzing intra- and interspecific relationships [ 6 ], and formulating protection strategies [ 7 ]. Additionally, seasonal dietary changes play a significant role in the avoidance of seasonal resource bottlenecks by herbivores [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%